Blocked 5′ Termini in Brome Mosaic Virus RNA - Dasgupta, Ranjit (1976)
All four components of brome mosaic virus RNA have m(7)G(5′) ppp (5′)Gp as their 5′ terminus. The m(7)G can be removed by β-elimination, resulting in the conversion to pppGp.